2005
DOI: 10.1097/01.pep.0000154185.55735.a0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Conditioning and Strength Training on a Child with Down Syndrome: A Case Study

Abstract: For this subject, a combined aerobic and strength-training program resulted in improved cardiopulmonary functions not observed in previous studies of subjects with DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 25 publications
4
52
0
6
Order By: Relevance
“…The strong correlation between muscle strength and VO 2 peak suggest that a combined strength training and aerobic conditioning program would be more effective in enhancing cardiovascular function in individuals with DS than aerobic training alone. This was confirmed by Lewis et al (2005) and Rimmer et al (2004) who found significant improvements in work capacity and cardiopulmonary function in DS individuals after a combined aerobic and resistance program.…”
Section: Strength Trainingsupporting
confidence: 62%
See 4 more Smart Citations
“…The strong correlation between muscle strength and VO 2 peak suggest that a combined strength training and aerobic conditioning program would be more effective in enhancing cardiovascular function in individuals with DS than aerobic training alone. This was confirmed by Lewis et al (2005) and Rimmer et al (2004) who found significant improvements in work capacity and cardiopulmonary function in DS individuals after a combined aerobic and resistance program.…”
Section: Strength Trainingsupporting
confidence: 62%
“…Thus, skeletal muscle weakness may be an important contributing factor to the lower oxygen consumption during maximal treadmill and cycle exercises observed in individuals with DS (Lewis et al, 2005). Furthermore, muscular fatigue may occur before the cardiovascular system is maximally stressed, although a treadmill/cycle test is designed to examine the maximal performance of the cardiovascular system rather than the skeletal muscle system.…”
Section: Strength Trainingmentioning
confidence: 99%
See 3 more Smart Citations